Ecosystem services in German infrastructure planning: A case study of the projected Lower Weser deepening - Nils Droste; Jasper N. Meya (Helmholtz-Zentrum für Umweltforschung (UFZ), 2015)
We study the incorporation of ecosystem services in German water infrastructure planning exemplified by a projected deepening of the Lower Weser river channel. Therefore, we recalculate the project's benefit-cost ratio by integrating the monetary value of changes in different ecosystem services: i) the restoration costs of a planned mitigation measure for a loss in fresh water supply for agricultural production in the estuary, ii) costs of loss in habitat services by transferring the willingness to pay between a contingent valuation study to the area assessed in the environmental impact assessment, and iii) the benefits of emission savings induced by more efficient shipping taking a marginal abatement cost approach. We find that the inclusion of monetary values for ecosystem service changes leads to a substantial drop in the benefit-cost ratio and consequently argue for a reform of the standard to facilitate more complete welfare assessments.
Keywords: 330; ecosystem services; cost-benefit analysis; infrastructure planning; river deepening; Germany